Application of UV responsive SiO2/PVP composite hydrogels as intelligent controlled drug release patches. (3rd January 2023) - Zhu, Wenqian; Zhao, Yanping; Wu, Zhiming; Lv, Fengzhu; Zhang, Yihe; Guo, Sufang
Abstract: Designing and preparing smart drug release systems are important in the field of medicine. A composite hydrogel preparation method is presented here to address the critical need and provide a practical perspective for local drug release. Photoresponsive silica polyvinylpyrrolidone (SiO2 -PVP) composite hydrogels were prepared based on the crosslinking effect of partially hydrolyzed tetraethyloxysilane and the flexibility of PVP to combine the advantage of SiO2 framework with more space and excellent deformation ability of PVP. Thus, the hydrogel prepared under optimized conditions was able to withstand 160% elongation and swell to 600%. In addition, relatively high drug loading and long-term release of ibuprofen for up to 10 h in solution were achieved. The hydrogel could even release drugs through the simulated skin and show a faster release rate under UV light irradiation and a higher surrounding temperature. The smart hydrogels had also been demonstrated to be biocompatible and non-toxic. The unique combination of strong mechanical properties, biocompatibility, and drug release properties may facilitate the application of hydrogels as skin patches. Graphical abstract: Image 1 Highlights: Photo-responsive composite hydrogels of SiO2 -PVP were prepared. The IBU release behaviors of the hydrogels through simulated skin were studied. The hydrogels showed excellent elongation and swelling rate. The hydrogels had the potential using as in vitro release systems as patches.